Good Will Hunting - Van Sant, Gus.; Williams, Robin, 1951-2014.; Damon, Matt.; Affleck, Ben, 1972-; Skarsgr̄d, Stellan; Driver, Minnie; Miramax Films; Miramax Home Entertainment (Firm); Buena Vista Home Entertainment (Firm) (Burbank, California : Miramax Home Entertainment : Distributed by Buena Vista Home Entertainment, 1998)
A young working-class genius is hauled back from the brink of self-destruction by a gifted counselor.
Title from disc.
Includes 11 deleted scenes with commentary, production featurette, theatrical trailer, TV commercials, Academy Award "Best Picture" montage, Miss Misery" music video, behind-the-scenes footage, and chapter search.
Dolby digital 5.1 audio, stereo.
"14888."
Director of photography, Jean Yves Escoffier ; editor, Pietro Scalia ; music, Danny Elfman.
Robin Williams, Matt Damon, Ben Affleck, Stellan Skarsgard, Minnie Driver.
Keywords: Feature films; Genius -- Drama; Genius and mental illness -- Drama; Video recordings for the hearing impaired